Acute effects of beetroot juice vs. creatine supplementation on maximal strength, autonomic regulation, and muscle oxygenation during incremental resistance exercise - Salem, Atef; Ammar, Achraf; Kerkeni, Mohamed; Boujelbane, Mohamed; Uyar, Ayse Merve; Köbel, Leonard Moritz; Selvaraj, Saranya; Zare, Reza; Heinrich, Katie M.; Jahrami, Haitham; Tounsi, Slim; Grosso, Giuseppe; et al. (Biology of Sport, 2025)
This study investigated the acute effects of beetroot juice (BJ) and creatine (CR) supplementation on maximal strength, heart rate variability (HRV), and muscle oxygenation during incremental resistance exercise. Eleven physically active males (age = 21.36±1.8 years) completed a randomized, double-blind, placebo-controlled, crossover protocol. Participants ingested either 0.3 g · kg −1 of CR or 15 g of beetroot powder (7.26 mmol·L −1 or 450 mg of nitrate) two hours before each session. The three testing sessions included bench press and back squat at 60%, 70%, and 80% of one-repetition maximum (1-RM) until failure. Repetition-to-failure, peak velocity, power, Heart rate, and muscle oxygen saturation (SmO 2 ) were recorded during both exercises. HRV indices, lower-limb strength performance, blood lactate, and rating of perceived exertion (RPE) were measured pre- and post-session. As intensity increased, maximum repetitions decreased significantly in all exercises and conditions ( p < 0.05). Both BJ and CR improved peak velocity compared to placebo ( p < 0.05). BJ led to lower peak heart rates at all intensities during BP and only at 80% of 1-RM during BS and higher SmO 2 across all intensities ( p < 0.05) compared to PLA and CR. From pre- to post session, lactate and RPE increased ( p < 0.05) and lower -limb strength performance and HRV declined ( p < 0.05), in all conditions, with no significant differences between BJ and CR. Compared to PLA, BJ showed significantly higher Root mean square of successive differences (RMSSD), Standard deviation of normal-to-normal intervals (SDNN), and high frequency (HF) power at both pre- and post-session ( p < 0.05). CR supplementation resulted in significantly higher RMSSD values compared to PLA at both pre- and post-session time points ( p < 0.001), while HF was significantly elevated only at post-session ( p = 0.018), and SDNN showed no significant differences at either time point. Additionally, BJ revealed significantly higher RMSSD than CR at pre-session ( p = 0.041). In conclusion, both BJ and CR significantly enhanced peak velocity during incremental resistance exercisescompared to placebo. However, BJ provided additional benefits in muscle oxygenation and autonomic nervous system regulation, particularly during high-intensity efforts.